Application of Asiatic Honey Bees (Apis cerana) and Stingless Bees (Trigona laeviceps) as Pollinator Agents of Hot Pepper (Capsicum annuum L.) at Local Indonesia Farm System. (29th December 2014) - Putra, Ramadhani Eka; Permana, Agus Dana; Kinasih, Ida
Abstract : In Indonesia, hot pepper ( Capsicum annuum ) is one of the most important spices. Despite the fact that high yield cultivars and fertilizers have been applied to increase the annual production of this spice, local farming is always unable to maintain constant production. Studies to find the explanation of this problem mostly focused on pest attack while possibility of low fruit production due to lack of pollination was neglected. In this study, the effect of pollinator visitation to fruit set and quality was assessed by application of two local domesticated honey bees, Asiatic honey bees ( Apis cerana ) and stingless bees ( Trigona laeviceps ) as potential pollinator agents at hot pepper plantation. This study found that both bees had similar visitation rate while A. cerana spend less time in flowers. Visitation by A. cerana and Trigona laeviceps improved fruit set, fruit production per plant, average fruit weight, and fruit size. This result confirms the importance of cross pollination for hot pepper production and both species could be used as pollination agent for hot pepper. Advantages and disadvantages for each species as pollination agent for local Indonesia farm system are discussed in this paper.